Oxford guide to the mind - Underwood Geoffrey (Oxford OUP, 2001)
This book represents an attempt to describe those human brain functions which are generally considered to be mental. The editor introduces each chapter with an overview, and experts writing sections of each make the information timely and accurate. The m
Keywords: Mind